The F type mitochondrial genome of hard-shelled mussel: Mytilus coruscus (Mytiloida, Mytilidae). (2nd January 2016) - Lee, Yu-Cheol; Lee, Youn-Ho
Abstract: We determined the complete mitochondrial genome of the female hard-shelled mussel Mytilus coruscus (Gould, 1869) (F type). The F type genome is composed of 16, 642 bp in length including 12 protein coding genes (PCGs), 2 rRNA and 23 tRNA with the same gene content and order as the other Mytilus species which is characterized by the absence of the ATPase8 gene and addition of tRNA Met (AUA). The nucleotide composition of the genome shows that the percentage of A+T (63.2%) is higher than those of M. edulis complex species ( M. edulis, M. galloprovincialis, M. trossulus ) but lower than that of M. californianus . The F type mitochondrial genome of M. coruscus will provide useful information on the evolutionary history of the Mytilus species in the family Mitilidae.